Penegakan Terhadap Pelaku Kejahatan Prostitusi Yang Dilakukan Oleh Mucikari - Sauma Aristi Pramudia; Bambang Joyo Supeno (Badan Penerbit STIEPARI Press, 2022)
Disclosure of criminal acts involving pimps is difficult to disclose because it is networked and covert which causes these crimes to not be resolved completely, besides that the sentence against pimps is too light so that the perpetrators will repeat their actions. Weaknesses in eradicating criminal acts of prostitution are due to the absence of statutory regulations or regional regulations in Central Java to prosecute prostitutes, the laws and regulations only ensnare pimps. Completion of this research 1) Enforcement of the crime of prostitution involving pimps in the legal area of ​​the Central Java Regional Police 2) Factors that cause pimps to commit criminal acts of prostitution in the Central Java Regional Police jurisdiction. Normative juridical research methods. Source of data, secondary data refers to literature, primary data refers to facts in the field and the results of interviews. Research results 1) Enforcement of perpetrators of prostitution crimes committed by pimps in the jurisdiction of Central Java can be charged using Articles 296 and 506 of the Criminal Code, known as Article bordeelhouderij based on the Criminal Decision of the Pati Court Number 16/Pid.Sus/2020/PN Pti in the event of a crime 2) Factors causing pimping for prostitution involving pimps in the jurisdiction of the Central Java Regional Police: a ) Internal factors include educational factors and individual factors b) External factors include economic factors, environmental factors , law enforcement factors, global development factors (technology). apprentices and externs are influential in cases of criminal acts of prostitution involving pimps because the perpetrators have an instant mindset to gain profits without thinking about the legal consequences of their actions violating Articles 296 and 506 of the Criminal Code, and can also be threatened with Article 2 of Law Number 21 of 2007 concerning Eradication of Criminal Acts of Trafficking in Persons.